2005
DOI: 10.1007/s00455-005-0027-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Removal of the Tracheotomy Tube on Swallowing During the Fiberoptic Endoscopic Exam of the Swallow (FEES)

Abstract: This study investigated the effects, if any, that the presence of a tracheotomy tube has on the incidence of laryngeal penetration and aspiration in patients with a known or suspected dysphagia. This was a prospective, repeated-measure design study. A total of 37 consecutive patients with a tracheotomy tube underwent a fiberoptic endoscopic evaluation of swallowing (FEES). Patients were first provided with pureed food boluses with the tracheotomy tube in place. The tracheotomy tube was then removed and the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 20 publications
5
22
0
6
Order By: Relevance
“…Specifically, no significant differences were found for either laryngeal excursion or hyoid bone displacement during swallowing based on the presence or absence of either the Passy Muir or Blom valve. This corroborates previous research which showed that presence/absence of a tracheotomy tube [3,4,8,9] and occlusion status of a tracheotomy tube [5][6][7]10] had no significant effect on hyolaryngeal movement. Aspiration status was also not effected by use of either the Passy-Muir or Blom one-way speaking valves.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Specifically, no significant differences were found for either laryngeal excursion or hyoid bone displacement during swallowing based on the presence or absence of either the Passy Muir or Blom valve. This corroborates previous research which showed that presence/absence of a tracheotomy tube [3,4,8,9] and occlusion status of a tracheotomy tube [5][6][7]10] had no significant effect on hyolaryngeal movement. Aspiration status was also not effected by use of either the Passy-Muir or Blom one-way speaking valves.…”
Section: Discussionsupporting
confidence: 94%
“…In a series of investigations, we have shown that presence/absence of a tracheotomy tube [3,4] and occlusion status of a tracheotomy tube [5][6][7] had no effect on either hyolaryngeal movement or incidence of aspiration. Independent investigators have corroborated these results for both presence/absence [8,9] and occlusion status [10] of a tracheotomy tube. Pharyngeal swallow biomechanics with a tracheotomy tube have been investigated with videofluoroscopy [4,11,12] and manometry [7].…”
Section: Introductionsupporting
confidence: 72%
“…In conjunction with the lack of a causal relationship between tracheotomy and aspiration, additional evidence supports the fact that the presence or absence of a tracheotomy tube is also irrelevant to swallowing success or failure [24][25][26]. Furthermore, research has shown that swallowing dysfunction can continue following decannulation [9] and, conversely, swallowing improvement can occur when the tracheotomy tube remains [11].…”
Section: Discussionmentioning
confidence: 96%
“…However, recent studies [37][38][39][57][58][59]] have failed to demonstrate causality between aspiration and tracheostomies per se as tracheostomies do not impair hyoid bone movement or laryngeal excursion during swallowing [60]. Instead, the severe illness necessitating the tracheostomy, whether neurological or not, and/or high dose medications [5] such as sedatives and neuromuscular blocking agents cause dysphagia, not the tracheostomy itself [37,38,58]. Another study found that tracheostomy removal did not change subjects' aspiration or dysphagic status [58].…”
Section: Tracheostomymentioning
confidence: 99%
“…Instead, the severe illness necessitating the tracheostomy, whether neurological or not, and/or high dose medications [5] such as sedatives and neuromuscular blocking agents cause dysphagia, not the tracheostomy itself [37,38,58]. Another study found that tracheostomy removal did not change subjects' aspiration or dysphagic status [58]. Tracheotomised patients with TBI are likely to be dysphagic because of their neurological impairment, medications [5], intercurrent medical co-morbidities [37], or a combination of these factors.…”
Section: Tracheostomymentioning
confidence: 99%